Penguatan Perpustakaan Untuk Pembangunan: Sebuah Konsep Transformasi Berbasis Inklusi Sosial - Wahyu Deni Prasetyo; Dian Utami (Ikatan Pustakawan Indonesia, 2020)
Goals of national development as the purpose of the “Pembukaan Undang-Undang Dasar 1945” are building a smart nation’s life and advancing public welfare. Library has a strategic role in national development by become a place who can used by people without limitation of social group. This concept is called library service based on social inclusion. In this article, the author tries to find definition of library service based on social inclusion and describe what changes are needed.